Experimental Investigations on Paver Blocks by Partial replacement of Cement by Lead slag and Natural sand by M-sand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Construction Industry plays a vital role in developing the economic growth of a country. Due to the rapid consumption of conventional raw materials such as sand and aggregates has resulted in non-availability of materials at the required time. This has made mankind to choose an alternative material such as M-sand, fly ash in construction projects. Lead battery manufacturing industries create a huge amount of by-products that are dumped into landfills. During the extraction of pure lead from exhausted batteries, it has resulted in the development of a by-product called lead slag during the smelting process. This material has found similarities in physical constituents with cement. Hence an attempt has been made to inculcate alternative materials during the manufacture of paver blocks. The concrete mix was designed for M30 grade. Materials such as Cement were replaced by Lead slag in varying percentages from 5%, 10%, 15%, and 20% respectively also Natural sand was replaced by 100% M-sand. From test results it was found that optimum content of lead slag that can be replaced is 15% without affecting the strength characteristics of paver blocks. This paper has also analyzed the cost involved for conventional and modified paver blocks per square feet.